Online health information seeking by adults hospitalized for acute coronary syndromes: Who looks for information, and who discusses it with healthcare providers?. Issue 11 (November 2018) - Waring, Molly E.; McManus, David D.; Amante, Daniel J.; Darling, Chad E.; Kiefe, Catarina I.
Highlights: 57% of online adults hospitalized with ACS seek health information online. More education, difficulty accessing care associated with information-seeking. Impaired numeracy, limited social networks negatively associated with info-seeking. 34% of information-seekers discussed online health information with providers. Education and frequent information-seeking associated with provider discussions. Abstract: Objective: To describe characteristics associated with online health information-seeking and discussing resulting information with healthcare providers among adults with acute coronary syndromes (ACS). Methods: Consecutive patients hospitalized with ACS in 6 hospitals in Massachusetts and Georgia who reported Internet use in the past 4 weeks (online patients) were asked about online health information-seeking and whether they discussed information with healthcare providers. Participants reported demographic and psychosocial characteristics; clinical characteristics were abstracted from medical records. Logistic regression models estimated associations with information-seeking and provider communication. Results: Online patients (N = 1142) were on average aged 58.8 (SD: 10.6) years, 30.3% female, and 82.8% non-Hispanic white; 56.7% reported online health information-seeking. Patients with higher education and difficulty accessing medical care were more likely to report information-seeking; patients hospitalized with myocardial infarction, and those with impaired health numeracy and limited social networks were less likely. Among information-seekers, 33.9% discussed information with healthcare providers. More education and more frequent online information-seeking were associated with provider discussions. Conclusion: Over half of online patients with ACS seek health information online, but only 1 in 3 of these discuss information with healthcare providers. Practice implications: Clinician awareness of patient information-seeking may enhance communication including referral to evidence-based online resources.